Desenvolvimento de um driver para LEDs aplicado à iluminação pública com reduzido processamento redundante de energia, entrada universal e controle de intensidade luminosa - Bekoski, Kleber Chan (2020)
This work presents the development of an LED driver for street lighting with universal input voltage and dimming that makes use of a connection with reduced redundant power processing. The need for drivers for powering LEDs is highlighted, and a review of the driving means is presented. A review of the drivers’ lifespan is carried out, and alternatives to make the driver and the LED compatibles in lifespan are discussed. A review of the topologies used in LED drivers is presented, and the partial cascade connection is selected. The SEPIC converter in discontinuous conduction mode is defined for the power factor correction stage, and the flyback converter also in the discontinuous conduction mode is set for the power control stage. The converters are modeled by the average switch model, and proportional-integral controllers are specified for the converters. To obtain experimental results, a 100 W prototype is built in the laboratory. The experimental results show the operating of the proposed LED driver for variation of the input voltage and variation of output power. The output current ripple is reduced with the control loops, and in all operating points, the flicker complies with the practical recommendation IEEE Std. 1789-2015. Is achieved efficiency above 90% is some operating points, and the 30% to 100% output power range the driver meets the requirements of IEC 61000-3-2 Class C for the entire input voltage range.